Breeding report of a new blueberry cultivar Farsight - WANG Xueting; GONG Xutong; LÜ Zixi; JI Xiangdong; ZHANG Wenji; WANG Nan; ZHAN Peihe; GAI Rongli; WANG Hexin; HAN Shiming; XU Guohui; WEN Lizhu (Guoshu xuebao, 2025)
The new blueberry variety, designated Farsight, is a southern highbush blueberry selected from seedlings of Bluerain. In spring 2011, 282 seedlings were obtained at Dalian Senmao Modern Agriculture Co., Ltd., and in spring 2012, the seedlings were transferred to Zhuanghe Experimental Station for field trials. The performance and characteristics of the seedlings were determined for mature fruits when they first fruited at the end of 2015. Based on the plant morphology, flowering and fruiting characteristics, fruit yield, and fruit quality, a superior offspring was selected and numbered SMN-035. SMN-035 showed excellent performance with vigorous plant growth, medium fruit size, light blue color, thick fruit wax, moderate acidity, small and dry picking scar, and high productivity. A comprehensive evaluation of the traits including plant morphology, fruit characteristics, and productivity were conducted from July 2017 to July 2019, demonstrating consistent and stable performance. In July 2020, the State Forestry and Grassland Administration granted this variety the Plant Cultivar Protection Certificate. This variety had an open tree form with very strong branching ability. The leaf blade was elliptical, the leaf margins were serrated, the leaf colour was dark green, and the back of the leaf was not tomentose. The leaf buds bursted earlier, the inflorescences were short, the corollas were altar-shaped with ridges, the anthocyanin colour intensity was medium. The fruits of the new fruiting shoots were in clusters, the fruits were closely attached to the spike, the fruits were oblate in shape, the average size of single fruit was 1.66 cm×1.79 cm, the maximum recorded weight of single fruit was 2.99 g, and the average weight was 2.59 g, the soluble solids content of the fruits was 10.68%. The fruits were light blue in colour (101-B), with thick wax, good flavour and a small and dry plucking scar. The fruits were excellent for fresh eating. The plant was vigorous and very productive. Under natural conditions in Dalian, Liaoning, the fruits matured at the end of June. It should be suitable for cultivation in the regions along the Yangtze River or areas in high altitudes.